POST-MERGER FINANCIAL AND STOCK PERFORMANCE ANALYSIS - , Vijayanti Satyaningsih ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Todayâs, there is a phenomenon in business world, a way to expand business activities by doing business combination. This research is focusing on one of business combinations which is merger. Merger is a combination of two (or more) firms in which one firm survives under its own name while the other ceases as a legal entity. The general reason for conducting merger is to gain synergy between acquiring company and target company. Despite of its many values that can be obtained by merger activity, such as to overcome financial problem, expose strategic opportunities and improve operational efficiency, this activity is also vulnerable to fail. The causes of these failures include compensation for managers, corporate culture and clarity of the fate of employees post-merger. The objective of this research is to determine the effect of merger in company performance and the shareholdersâ welfare. This research used data for five financial ratios (current ratio, total assets turnover ratio, debt ratio, return on equity and price per earnings ratio) to measure the companyâs financial performance and stock price to measure the share performance from year 1998 until 2008. The total sample is 10 companies, based on criteria the non-financial companies that listed in Indonesia Stock Exchange and merged in period 2000-2008. The t-test of paired two samples means, both for financial and stock performance analysis will be used to compare means the variables at before and after merger. As the result, financial performances in two years before and two years after merger are not statistically significant different. The other results, abnormal return during windows period, in 45 days before and 45 days after merger are statistically significant different between stock performance before and after merger. From the analysis, it can be conclude that merger does not have positive influence to the financial and stock performance. This is because companies do not pay attention to the aspects that can cause failure of the merger.